Deteksi Tepi Danau Pada Citra Satelit Menggunakan Metode Canny - Koko Pradityo; Budi Darma Setiawan; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Lake is an important land feature for human life. Changes in a lake's condition would affect the environment and the people living nearby. One of the method being used to detect changes in lake's condition is by using an edge detection of the lake based on satellite image for further analysis such as measuring the change in lake's total area. Appropriate implementation and optimization of such algorithm can lead to a better analysis of the lake's condition. In this research, the system implemented Canny Edge Detection algorithm to detect the edge of a lake on a satellite image. A segmentation algorithm based on color thresholding is used to improve the edge detection algorithm. The test result shows that Canny Edge Detection algorithm has 57% error detection rate, while segmentation process using color thresholding improves the detection performance by 67%.